Distance Learning of Foreign Languages through Virtual Reality. - Собков, Юрій; Кондратюк, Леся; Мусійчук, Світлана; Зуєнко, Нелля; Требик, Олег; Єфімов, Дмитро (BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 2022)
The article is devoted to virtual reality technologies and scenarios of their application in distance learning of foreign languages. A generalized experience of application of virtual reality technologies in distance learning of foreign languages is presented; the advantages, risks and deterrents of their introduction into the educational process in educational institutions are highlighted. The features by which technologies can be classified as virtual reality technologies are singled out. Examples of application of the following virtual reality technologies are considered: Mondly VR, VirtualSpeech, Immersive VR Education, AltspaceVR and ClassVR; their brief description, scenarios for use in learning foreign languages, benefits and risks of use are provided. Summarizing the review of these technologies, it was found that the educational content of distance learning of foreign languages through virtual reality can be divided into three groups: “360-degree video”, platforms and sites, interactive programs. Conditions and didactic principles of the effective use of virtual reality technologies during distance learning of foreign languages are generalized. The issue of assessing effectiveness of virtual reality technologies in learning foreign languages is analyzed and identified as debatable and in need of further research. The criteria by which researchers summarize the principles of selection of evaluation criteria are clarified. Perspective directions of future scientific investigations are outlined: research of conditions of intensification and research of scenarios of use of collective intelligence during distance learning of foreign languages through virtual reality.
Keywords: Distance learning, virtual reality technologies, immersive technologies, language environment.